Bet v 1 contiguous overlapping peptides anchored to virosomes with TLR4 agonist enhance immunotherapy efficacy in mice. Issue 2 (6th January 2021) - Airouche, Sabi; Beltrami, Vanya; Fleury, Sylvain; Batard, Thierry; Bordas‐Le Floch, Véronique; Stegmann, Toon; Amacker, Mario; Kettner, Alexander; Mascarell, Laurent
Abstract: Background: Whereas sublingual allergen immunotherapy (AIT) is routinely performed without any adjuvant or delivery system, there is a strong scientific rationale to better target the allergen(s) to oral dendritic cells known to support regulatory immune responses by using appropriate presentation platforms. Objective: To identify a safe presentation platform able to enhance allergen‐specific tolerance induction. Methods: Virosomes with membrane‐integrated contiguous overlapping peptides (COPs) of Bet v 1 and TLR4 or TLR2/TLR7 agonists were assessed for induction of Bet v 1–specific IgG1, IgG2a and IgE antibodies, hypersensitivity reactions and body temperature drop following subcutaneous injection in naive CD‐1 mice. The most promising candidate, Bet v 1 COPs anchored to virosomes with membrane‐incorporated TLR4 agonist (Vir.A‐Bet v 1 COPs), was further evaluated by the sublingual route in a therapeutic setting in BALB/c mice with birch pollen‐induced allergic asthma. Airway hyperresponsiveness, pro‐inflammatory cells in bronchoalveolar lavages and polarization of Th cells in the lungs and spleen were then assessed. Results: Both types of adjuvanted virosomes coupled to Bet v 1 COPs triggered a boosted Th1 immunity. Given a more favourable safety profile, Vir.A‐Bet v 1 COPs were further evaluated and shown to able to fully reverse asthma symptoms and lung inflammation in a sublingual therapeutic model of birch pollen allergy. Conclusions and Clinical Relevance: We report herein for the first time on the capacity of a novel and safe presentation platform, that is virosomes with membrane‐integrated TLR4 agonist, to improve dramatically sublingual AIT efficacy in a murine model due to its intrinsic dual properties of targeting and stimulating to further promote anti‐allergic immune responses. As such, our study paves the ground for further clinical development of this allergen presentation platform for patients suffering from respiratory allergies.